Adherence to HEp-2 cells and 0 Serotypes diversity of indigenous enteropathogenic Escherichia coll. - Sri Budiarti, Sri Budiarti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
Enteropathogenic Escherichia coil (EPEC) is bacteria which causes diarrhea! diseases especially in children. Sixty-nine children with diarrheal disease from Purwodadi Central Java, Depok, Ciamis and Ciawi West Java also Sambas, West Kalimantan have been detected to the presence of EPEC bacteria. The prevalence of EPEC bacteria in each area were 46%, 66%, 68%, 46%, and 50% respectively. All of isolates have been tested for their ability of adherence to HEp-2 cells and 0 serotype. The results showed that 0 86 and 0111 were present in all sampling area but 0142 was only found in Depok and Ciamis Central Java at high percentages. There was no correlation between the ability of adherence to HEp-2 cells and serotype diversity.Key words: diarrhea - children - 0 Serotype - enteropathogenic Escherichia coil - HEp-2 cells.